1923
DOI: 10.1002/cber.19230560110
|View full text |Cite
|
Sign up to set email alerts
|

Über die Farbe der γ,γ′‐Dipyridylium‐halogenide

Abstract: angefiihrten LBsungen in Chinolin findeii sich in der dcmnichst erscheinenden Arbeit und werden hier nicht nochmals angefiihrt. Erwihnt sei nur iioch, daO die Durchrechnung der C h i 1 e s o t 1 i schen Daten fiir das P h e n a n t h r e n und A n t h r a c e n keinc hrauclibaren ES-Werte liefertc, jedoch sei von der Wiedergabe dieser Berechuungen abgesehcn. M a r b u r g , Chemisches Institut. 9. Bruno Emmert und Julius S t a w i t z : ober die Farbe der y,f-Dipyridylium-halogenide. [Aus d. Chem. Institut d. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
1

Year Published

1925
1925
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…[32,33] However, it has been shown that this reaction can also be applied to 2-methylpyridine. [34,35] Thus, N-substituted pyridine-2-thiocarboxamides have been prepared by reaction of 2-methylpyridine with primary amines, [34,35] nitro compounds, [34] or N-substituted formamides [16,36] as amine sources in the presence of sulfur at elevated temperatures Scheme 2. Possible amine sources for the synthesis of N-substituted pyridine-2-thiocarboxamides under the conditions of the WillgerodtϪKindler reaction Eur.…”
mentioning
confidence: 99%
“…[32,33] However, it has been shown that this reaction can also be applied to 2-methylpyridine. [34,35] Thus, N-substituted pyridine-2-thiocarboxamides have been prepared by reaction of 2-methylpyridine with primary amines, [34,35] nitro compounds, [34] or N-substituted formamides [16,36] as amine sources in the presence of sulfur at elevated temperatures Scheme 2. Possible amine sources for the synthesis of N-substituted pyridine-2-thiocarboxamides under the conditions of the WillgerodtϪKindler reaction Eur.…”
mentioning
confidence: 99%
“…Similar but weaker spectral effects were found for other donor molecules like EDTA, nitrilotriethanol, or ascorbate. Charge-transfer complexation has been observed and studied for methylviologen (4) itself (see for instance [7][8][9][10][11][12][13][14][15][16][17][18][19]), but the corresponding absorptions are markedly stronger in the VIS for 1 as compared to 4 (with indole acetate, E = 200 and 20, respectively; aqueous solution, 5 mM of each compound; for 4 see also [15]). In view of the numerous studies which have been devoted to the spectroscopic, photophysical, and photochemical properties of 4 (including its use as redox relay species in photochemical light energy storage cycles, see below), MeDAP" (1) and its derivatives represent excellent candidates for The diazapyrenium cations show strongfluorescence (Fig.…”
mentioning
confidence: 99%
“…Bei den quartaren Ammoniumionen mit einem polaren Substituenten wird dieser reduktiv abgespalten [21,22] NMeaX + e -+ NMeaX;d' NMeaX~d + H+ + e -+ NMe a + HX .…”
unclassified